1997
DOI: 10.1002/ana.410410108
|View full text |Cite
|
Sign up to set email alerts
|

Activation mapping in essential tremor with functional magnetic resonance imaging

Abstract: We used functional magnetic resonance imaging (FMRI) to study possible cerebral activation patterns associated with unilateral postural tremor in 12 patients with essential tremor (ET), with mimicked postural tremor in 15 control subjects, and with passive wrist oscillation in both groups. During essential tremor, patients showed mainly contralateral activation of the primary motor and primary sensory areas, the globus pallidus, and the thalamus, but bilateral activation of the nucleus dentatus, the cerebellar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
150
2
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(166 citation statements)
references
References 32 publications
11
150
2
2
Order By: Relevance
“…Moreover, an autopsy study of humans with chronic organic lead exposure revealed severe destruction of cerebellar Purkinje cells (Valpey et al 1978). Multiple lines of evidence suggest that the cerebellum is involved in ET, including imaging studies [positron emission tomography (Wills et al 1994), functional magnetic resonance imaging (Bucher et al 1997), and magnetic resonance spectroscopic imaging (Louis et al 2002a)], clinical studies and electrophysiologic studies Gironell et al 2000;Stolze et al 2000), and case reports (Dupuis et al 1989). Unfortunately, there have been few postmortem studies of ET; several studies revealed loss of cerebellar Purkinje cells, but without control brains for comparison, these results are difficult to interpret (Louis 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, an autopsy study of humans with chronic organic lead exposure revealed severe destruction of cerebellar Purkinje cells (Valpey et al 1978). Multiple lines of evidence suggest that the cerebellum is involved in ET, including imaging studies [positron emission tomography (Wills et al 1994), functional magnetic resonance imaging (Bucher et al 1997), and magnetic resonance spectroscopic imaging (Louis et al 2002a)], clinical studies and electrophysiologic studies Gironell et al 2000;Stolze et al 2000), and case reports (Dupuis et al 1989). Unfortunately, there have been few postmortem studies of ET; several studies revealed loss of cerebellar Purkinje cells, but without control brains for comparison, these results are difficult to interpret (Louis 2001).…”
Section: Discussionmentioning
confidence: 99%
“…As such, ET is one of the most common neurologic diseases. The pathogenesis of this progressive ) and often disabling (Louis et al 2001a) disease is poorly understood, although there is evidence of cerebellar involvement (Bucher et al 1997;Louis et al 2002a;Wills et al 1994). There is no cure for ET, and there has been no attempt to favorably modulate or halt its progression with neuroprotective therapy.…”
mentioning
confidence: 99%
“…48 These pontine structures were also implicated by measures of blood flow with fMRI. 49 Bilateral activation of the red nucleus, along with the dentate nuclei and both cerebellar hemispheres, was observed in patients with ET, while control subjects only showed unilateral activation of these regions when they affected tremor with the opposite limb. PET research has also provided a neurologic explanation for the above-mentioned fact that consumption of ethanol modulates ET.…”
Section: The Dysfunctional Correlates Of Etmentioning
confidence: 95%
“…Although postmortem studies point towards cerebellar changes, PET and fMRI studies have revealed abnormalities in the cerebellum, thalamus, and triangle of Guillain-Mollaret, which is settled in the brain stem and inferior olive nucleus. Researchers argue that the postural tremor of ET arises from spontaneous firing of inferior olivary nucleus (ION), which connects the cerebellum and its output pathways to the cerebral cortex and then to the spinal cord through VIM of the thalamus (11,12,13,14,15,16,17). Studies have shown that ET amplitude could be significantly reduced with thalamic lesions or thalamic stimulation, and the thalamus has been suggested to play a major role in the formation or transmission of ET (18,19).…”
Section: Discussionmentioning
confidence: 99%